Genetic Correlations of Brain Lesion Distribution in Multiple Sclerosis: An Exploratory Study - Sombekke, M.H.; Vellinga, M.M.; Uitdehaag, B.M.J.; Barkhof, F.; Polman, C.H.; Arteta, D.; Tejedor, D.; Martinez, A.; Crusius, J.B.A.; Peña, A.S.; Geurts, J.J.G.; Vrenken, H. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: In MS, the total brain lesion volume and spatial distribution of lesions across the brain vary widely among individual patients. We hypothesized that spatial distribution may be partially driven by genetic predisposition, and we aimed to explore relations among candidate genes and the spatial distribution of white matter brain lesions in MS. MATERIAL AND METHODS: Genotypes of 69 SNPs in 208 patients with MS were related to the spatial distribution of T2 brain lesions. Lesions were manually outlined on MR images, and binary lesion masks were produced and registered to a common space. With Randomise software, the lesion masks were related to genotype by using a voxelwise nonparametric GLM approach, followed by clusterwise analysis. We used a DNA chip with SNPs selected from the literature on MS susceptibility, severity, and phenotypes. RESULTS: For 11 of these SNPs, 1 of the genotypes expressed significant clusters of increased or decreased lesion probability in varying, predominantly periventricular, brain regions. When we statistically controlled the voxelwise analyses for effects of total brain lesion volume, only 1 SNP remained significant: rs2227139, located within the MHC class II region. This SNP retained its periventricular cluster of significantly increased lesion probability for the heterozygote genotype. CONCLUSIONS: Heterozygosity of rs2227139 (MHC class II region) is associated with increased right frontal periventricular lesion probability (P < .01). Ten other SNPs showed associations between genotype and spatial lesion distribution that are partly explained by total lesion volume. BTNL2butyrophilin-like 2CCL5chemokine (C-C motif) ligand 5CCR5chemokine (C-C motif) receptor 5CNScentral nervous systemCRYABα B crystallinEAEexperimental autoimmune encephalomyelitisEDSSExpanded Disability Status ScaleFAStumor necrosis factor receptor superfamily, member 6FLIRTFMRIB Nonlinear Image Registration ToolFSLFMRIB Software LibraryFMRIBFunctional MR Imaging of the BrainGLMgeneral linear modelHLAhuman leucocyte antigenHLA-DRB1major histocompatibility complex, class II, DRB1 (Homo sapiens)IFNGR2interferon gamma receptor 2 (interferon γ transducer 1)IQRinterquartile rangeLPMlesion probability mappingMAFminor allele frequencyMHCmajor histocompatibility complexMSmultiple sclerosisNADHnicotinamide adenine dinucleotideNDUFS7NADH dehydrogenase (ubiquinone) Fe-S protein 7PNMTphenylethanolamine N-methyltransferasePPMSprimary-progressive MSRRMSrelapsing-remitting MSrs-nrRefSNP accession IDSNPsingle nucleotide polymorphismSPMSsecondary-progressive MSUCP2uncoupling protein 2